Analisis Tipe-Tipe Kepemimpinan Dalam Meningkatkan Kinerja Koperasi Sekolah : Analisis Tipe-Tipe Kepemimpinan Dalam Meningkatkan Kinerja Koperasi Sekolah - Sefia Sefia Nabila; Muhammad Fatchurrizqi; Tariska Dina Aulina; Siswadi (STKIP Subang, 2026)
School cooperatives are an important medium for supporting economic learning and character development among students through entrepreneurial activities. The success of school cooperatives is strongly influenced by the role of leadership in their management. This article aims to analyze the types of leadership in improving the performance of school cooperatives. The method used is a qualitative descriptive approach with a literature study based on various sources such as books, scientific journals, and relevant previous research. The results of the study indicate that each leadership style has a different impact on the performance of school cooperatives. Transformational leadership is proven to enhance motivation, innovation, and member participation through inspiration and individualized consideration. Democratic leadership provides opportunities for participation in decision-making, thereby increasing members’ sense of responsibility. Meanwhile, transactional leadership contributes to improving discipline through a system of rewards and punishments. Autocratic leadership accelerates decision-making processes but may reduce member participation if not applied proportionally. In contrast, laissez-faire leadership gives members freedom but may lead to a lack of direction in management. Overall, transformational and democratic leadership are considered the most effective in improving school cooperative performance as they create a balance between motivation, participation, and innovation within the organization.